Podcast in the metaverse? exploring the unknown - Rocha, Angelo Eduardo (2024)
Stephenson's 1992 'metaverse' resurfaces in the form of platforms (plural). A single integrated Virtual Reality world is still not at all solid and accessible. In exploring the unknown, the article systematizes the characteristics of 163 podcast records in metaverse spaces published on YouTube. In order to carry out a panorama of podcast in metaverse, the methodological processes adopted were state of the art and quanti-quali analysis. The analysis describes the first experiences, the number of videos per year, platforms used, main producers, predominant language in the videos, duration and themes of the productions. As a result, it was noted that the big five do not yet have a leading role in the seed, the production is still amateur, but specialized on the themes of Virtual Reality, game and metaverse.